Perilaku Hidup Bersih Dan Sehat Terhadap Personal Higiene Siswa Sekolah Dasar Negeri 10 Benteng Kabupaten Sidrap - Rosdiana Rosdiana (Departement of Mathematics Education, 2022)
The prevalence of National Standard Clean and Healthy Living Behavior is 38.7% nationally. Sulawesi has 36.2% healthy lives from the indicators, namely healthy houses 85,827, sample 53,964 houses (62.9%), TTU 359, 87.74, healthy water 95.39%, latrines 65.30%. Research Objective: To find out whether there is a relationship between knowledge about clean and healthy living and the personal hygiene of students at Negeri 10 Benteng Sidrap District Elementary School. Research Method: The research design used is an analytical study, stratified random sampling method, the research population is all students at Negeri 10 Benteng Sidrap Regency Elementary School, while the sample to be taken is 44 respondents. Research Results: Research results from 44 respondents, independent variables, namely knowledge and the dependent variable of student cleanliness, data obtained from respondents using a questionnaire, chi-square statistical test, level of confidence p = α (0.05), namely knowledge about Clean Living Behavior and Healthy (P= 0.00). Conclusion: There is a relationship between knowledge about clean and healthy living behavior and personal hygiene of students at Negeri 10 Benteng Sidrap District Elementary School